Efficient synthesis of 2-oxazolidinones and quinazoline-2, 4(1H, 3H)-diones from CO2 catalyzed by tetrabutylammonium fluoride. Issue 24 (14th June 2018) - Fujii, Akira; Matsuo, Hideaki; Choi, Jun-Chul; Fujitani, Tadahiro; Fujita, Ken-ichi
Abstract: By employing tetrabutylammonium fluoride (TBAF) as a catalyst, the various carboxylative cyclizations of the propargylic amines having internal alkynes with CO2 proceeded to afford the corresponding 2-oxazolidinones. In this case, it was also found that the generated 2-oxazolidinones were tautomerized into the corresponding 2-oxazolones due to the basicity of TBAF. In addition, we performed the synthesis of quinazoline-2, 4(1 H, 3 H )-dione from 2-aminobenzonitrile and CO2 by using TBAF as a catalyst. Graphical abstract: